Cellulose‐based Supercapacitors: Material and Performance Considerations. Issue 18 (9th May 2017) - Wang, Zhaohui; Tammela, Petter; Strømme, Maria; Nyholm, Leif
Abstract : One of the biggest challenges we will face over the next few decades is finding a way to power the future while maintaining strong socioeconomic growth and a clean environment. A transition from the use of fossil fuels to renewable energy sources is expected. Cellulose, the most abundant natural biopolymer on earth, is a unique, sustainable, functional material with exciting properties: it is low‐cost and has hierarchical fibrous structures, a high surface area, thermal stability, hydrophilicity, biocompatibility, and mechanical flexibility, which makes it ideal for use in sustainable, flexible energy storage devices. This review focuses on energy storage applications involving different forms of cellulose (i.e., cellulose microfibers, nanocellulose fibers, and cellulose nanocrystals) in supercapacitors, with particular emphasis on new trends and performance considerations relevant to these fields. Recent advances and approaches to obtaining high capacity devices are evaluated and the limitations of cellulose‐based systems are discussed. For the first time, a combination of device‐specific factors such as electrode structures, mass loadings, areal capacities, and volumetric properties are taken into account, so as to evaluate and compare the energy storage performance and to better assess the merits of cellulose‐based materials with respect to real applications. Abstract : The most exciting recent advances in the supercapacitor application of cellulose composites based on different types of cellulose are summarized. In particular, this work focuses on parameters of cellulose‐based electrodes which affect the overall capacity performance metrics of supercapacitors. Approaches toward the realisation of high active masses and high volumetric capacitances for cellulose based electrodes are discussed.